2019
DOI: 10.1556/019.70.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids production and antioxidant properties in Catharanthus roseus (L.) G. Don. shoots and study of alkaloid biosynthesis-related gene expression levels in response to methyl jasmonate and putrescine treatments as eco-friendly elicitors

Abstract: Alkaloids production and antioxidant properties in Catharanthus roseus (L.) G. Don. shoots and study of alkaloid biosynthesisrelated gene expression levels in response to methyl jasmonate and putrescine treatments as ecofriendly elicitors. Biol. Fut. 70,[38][39][40][41][42][43][44][45][46]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Consistent with these findings, an increase has been reported in the accumulation of vindoline in the transgenic Datexpressing plants [12]. Furthermore, MeJA and putrescine treatments have been shown to lead to the up-regulation of Str, Prx1, Dat genes and consequently the production of vincristine and vinblastine alkaloids [35]. In another study, foliar application of SA on the leaves of C. roseus seedlings exposed to drought and salinity stresses increased the transcript level of the Dat and D4h genes [11].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Consistent with these findings, an increase has been reported in the accumulation of vindoline in the transgenic Datexpressing plants [12]. Furthermore, MeJA and putrescine treatments have been shown to lead to the up-regulation of Str, Prx1, Dat genes and consequently the production of vincristine and vinblastine alkaloids [35]. In another study, foliar application of SA on the leaves of C. roseus seedlings exposed to drought and salinity stresses increased the transcript level of the Dat and D4h genes [11].…”
Section: Discussionsupporting
confidence: 62%
“…DAT converts deacetylvindoline into vindoline in the TIAs alkaloid pathway [15,6,8]. An increase in the expression level of Dat has been found to result in the accumulation of vinblastine and vincristine alkaloids [12,35]. Inoculation of C. roseus with fungal endophytes led to an increase in the expression of Str, D4h and Dat genes and consequently vindoline content C. roseus increased [30].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the positive correlation between relative expression level of these gene and the accumulation of corresponding alkaloids in C. roseus (Dutta et al, 2005;Goklani et al, 2009;Jaggi et al, 2011 andWang et al 2016), it can be concluded that up-regulation of G10H, DAT, T16H and CrPRX genes under these treatments, especially by P. uorescens, can result in a higher production rate of vinblastine and vincristine alkaloids as nal products in the TIA biosynthetic pathway. As an example, it is shown that an increase in the expression level of DAT has been found to result in the accumulation of vinblastine and vincristine alkaloids (Wang et al, 2012 andKhataee et al, 2019). In this case, metabolite studies were performed in the plant.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK has been known to play an important function in plant responses, triggered by ROS, through dynamic gene expression and regulations. It has been reported to be crucial for flavonoid [80] and alkaloid [81] biosynthesis when plants are subjected to stress conditions. Paezi et al [82] reported up-regulation of several genes involved in the biosynthesis of alkaloids, coupled with high expression of Mitogen-Activated Protein Kinase 3 (CrMPK3) gene on Catharanthus roseus after silver exposure.…”
Section: Possible Mechanism Of Agnps In Plant Cellsmentioning
confidence: 99%